Development of a contextual-based digital book to improve short story writing skills - Rani Adillah; Abdurahman Adisaputera; Wildansyah Lubis (Himpunan Pengembang Kurikulum Indonesia, 2025)
The current technological development has challenges in seeing the condition of Indonesian language learning in elementary schools, which is still dominated by theoretical approaches. The ability to write is not just composing words, but a reflection of scientific, creative and structured thinking processes that must be honed gradually from an early age. This study aims to develop a context-based digital book using the Project-Based Learning model to enhance elementary school students’ short story writing skills. The research employed a Research and Development (RnD) method using the 4-D model consisting of Define, Design, Develop, and Disseminate stages. The research subjects were fifth-grade students of SD Swasta Sinar Husni in Medan. Research instruments included a writing skill test and expert validation questionnaires based on writing indicators and media feasibility criteria. Validation results from content, media, and design experts indicated that the developed digital book was highly valid and suitable for use in instructional settings. The effectiveness test revealed significant improvements in students’ writing skills, particularly in idea development, logical story structure, and the accurate use of language and punctuation. The implementation also resulted in increased student engagement, learning motivation, and involvement in writing activities based on real-life experiences. These findings suggest that context-based digital books integrated with Project-Based Learning can serve as an effective and practical instructional medium, especially in developing narrative writing skills that are systematic, relevant, and creative for primary school students. Abstrak Perkembangan teknologi saat ini memiliki tantangan dalam melihat kondisi pembelajaran bahasa Indonesia di sekolah dasar yang masih didominasi pendekatan teoritis. Kemampuan menulis tidak sekadar menyusun kata, tetapi menjadi cerminan proses berpikir ilmiah, kreatif, dan terstruktur yang harus diasah secara bertahap sejak dini. Penelitian ini bertujuan untuk mengembangkan buku digital berbasis pendekatan kontekstual dengan menggunakan model Project Based Learning guna meningkatkan keterampilan menulis cerita pendek peserta didik sekolah dasar. Penelitian menggunakan metode Research and Development (RnD) dengan model pengembangan 4-D yang terdiri atas tahap Define, Design, Develop, dan Disseminate. Subjek dalam penelitian ini adalah peserta didik kelas V SD Swasta Sinar Husni Kota Medan. Instrumen penelitian mencakup tes keterampilan menulis dan angket validasi yang disusun berdasarkan indikator menulis serta kelayakan media pembelajaran. Hasil validasi oleh ahli materi, ahli media, dan ahli desain menunjukkan bahwa produk yang dikembangkan berada pada kategori sangat valid dan layak digunakan. Hasil uji keefektifan menunjukkan bahwa terdapat peningkatan signifikan keterampilan menulis peserta didik, khususnya pada aspek pengembangan ide, penggunaan struktur cerita yang logis, serta ketepatan bahasa dan ejaan. Implementasi buku digital ini juga menunjukkan peningkatan partisipasi aktif peserta didik, motivasi belajar, dan keterlibatan dalam kegiatan menulis berbasis pengalaman nyata. Temuan ini merekomendasikan bahwa buku digital berbasis pendekatan kontekstual dapat menjadi alternatif media pembelajaran yang efektif, aplikatif, dan sesuai dengan kebutuhan peserta didik sekolah dasar, khususnya dalam meningkatkan kemampuan menulis naratif secara sistematis dan kreatif. Kata Kunci: buku digital; keterampilan menulis; pendekatan kontekstual; project based learning